2021
DOI: 10.1126/scitranslmed.abf5965
|View full text |Cite
|
Sign up to set email alerts
|

Pantothenate kinase activation relieves coenzyme A sequestration and improves mitochondrial function in mice with propionic acidemia

Abstract: Therapeutic relief of CoA sequestration improves mitochondrial dysfunction in a propionic acidemia mouse model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(63 citation statements)
references
References 100 publications
1
59
0
Order By: Relevance
“…These results support a model whereby the hypermorphic PANK3 G193A mutation drives the accumulation of supraphysiological acetyl-CoA concentrations that effectively compete with the drug at the HAT active site. To validate this orthogonally, we used a smallmolecule PANK agonist, PZ-3022, that increases cellular levels of acetyl-CoA 44 . As expected, treatment with this compound reduced sensitivity to CBP/p300 HAT inhibitors but did not affect sensitivity to CBP/p300 bromodomain inhibitors (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These results support a model whereby the hypermorphic PANK3 G193A mutation drives the accumulation of supraphysiological acetyl-CoA concentrations that effectively compete with the drug at the HAT active site. To validate this orthogonally, we used a smallmolecule PANK agonist, PZ-3022, that increases cellular levels of acetyl-CoA 44 . As expected, treatment with this compound reduced sensitivity to CBP/p300 HAT inhibitors but did not affect sensitivity to CBP/p300 bromodomain inhibitors (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…BBP-671 treatment activates the PANK3 isoform to increase CoA production that, in turn, has a direct role on TCA cycle metabolism (Fig. 1) [5] and hence Glx production. In contrast to our findings, a study performed on 3 human PKAN patients reported an increase of Glx in the white matter [25].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1a depicts the effects of loss of CoA synthesis due to disruption of murine Pank1 and Pank2 genes in neurons. Pyruvate produced from glycolysis requires CoA to form acetyl-CoA, a substrate for the mitochondrial TCA cycle, and CoA limitation can disrupt TCA cycling [5] which, in turn, affects glutamate metabolism thereby causing cell death [6,7] (Fig. 1a).…”
Section: Open Accessmentioning
confidence: 99%
“…A recent analysis of a hypomorphic mouse model of PA suggests that reduced cellular CoASH triggers mitochondrial dysfunction and represents an underlying metabolic crisis in PA 7 . CoASH functions as a cofactor in numerous reactions in intermediary metabolism and is a critical substrate for two key steps in mitochondrial energy metabolism: pyruvate and α‐ketoglutarate dehydrogenases.…”
Section: Introductionmentioning
confidence: 99%